Effect of hydrate anti-agglomerants on water-in-crude oil emulsion stability - Azizi, A. (Springer, 2020)
Under high-pressure and low-temperature conditions, gas hydrate shells may form and grow at the interface of water droplets in water-in-oil emulsions. Such hydrate formation can enable downstream agglomeration and slurry viscosification, thus increasing the risk of hydrate blockage. Therefore, emulsion stability represents a critical parameter in understanding this overall flow behaviour. In this study, the impact of three common and widely-used industrial anti-agglomerants from three different suppliers (AA-1, AA-2 and AA-3âexact composition is commercially sensitive) on 30 wt water-in-oil (W/O) emulsion stability was investigated. Bench-top nuclear magnetic resonance (NMR) pulsed field gradient (PFG) methods were used to measure the droplet size distributions (DSDs) of the W/O emulsions as a complement to bottle stability test. In the absence of hydrate anti-agglomerants, based on visual observation, 85 of the original W/O emulsion remained after 10Â h. In the presence of AA-1 and AA-2, 94 of the original emulsion was retained; in contrast, AA-3 acted to destabilise the emulsion with only 64 of the original emulsion visually evident after 10Â h. These results were substantiated by PFG NMR measurements which showed substantial changes in droplet size as a function of sample height for the W/O emulsion formulated with AA-3. Interestingly the W/O emulsion formulated with AA-1, while very stable, was characterised by comparatively very large waterÂ droplets, indicative of a complex multiple water-in-oil-in-water (W/O/W) emulsion microstructure. AA-2 forms stable emulsion with small droplets of water dispersed in the oil phase. Our results provide insight into a wide range of potential impacts of AA addition on an industrial crude oil pipeline, in which AA-1 resulted in a complex W/O/W multiple emulsion, AA-2 behaved as an emulsifier and AA-3 behaved as a demulsifier. Â© 2019, The Author(s).